2018
DOI: 10.1002/ijop.12564
|View full text |Cite
|
Sign up to set email alerts
|

The longitudinal associations between personal belief in a just world and teacher justice among advantaged and disadvantaged school students

Abstract: The Just World Hypothesis states that people need to believe in a just world in which they get what they deserve and deserve what they get. This study examines the longitudinal associations between personal belief in a just world (BJW), the belief that events in one's own life are just and teacher justice in different status groups. It is posited that the more individuals believe in a personal just world, the more they feel they are treated justly by others, and this should be particularly true for students wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Secondary school students' PBJW was positively associated with both teacher justice (e.g., Dalbert & Stoeber, 2005;Kiral Ucar & Dalbert, 2018) and classmate justice (e.g., Correia & Dalbert, 2007). In addition, studies have shown that teacher justice (e.g., Dalbert & Stoeber, 2005;Donat, Peter, Dalbert, & Kamble, 2016; and classmate justice (e.g., Correia & Dalbert, 2007) mediated the relation between secondary school students' PBJW and various indicators of well-being, including life satisfaction.…”
Section: The Mediating Role Of Justice Experiencesmentioning
confidence: 94%
See 1 more Smart Citation
“…Secondary school students' PBJW was positively associated with both teacher justice (e.g., Dalbert & Stoeber, 2005;Kiral Ucar & Dalbert, 2018) and classmate justice (e.g., Correia & Dalbert, 2007). In addition, studies have shown that teacher justice (e.g., Dalbert & Stoeber, 2005;Donat, Peter, Dalbert, & Kamble, 2016; and classmate justice (e.g., Correia & Dalbert, 2007) mediated the relation between secondary school students' PBJW and various indicators of well-being, including life satisfaction.…”
Section: The Mediating Role Of Justice Experiencesmentioning
confidence: 94%
“…In detail, Gerhards (2010) described that Turkish citizens prefer a traditional male-dominated gender order and show an affinity to a more authoritarian regime. Despite these cultural differences, no significant differences of the PBJW have been identified between German and Turkish students (Kiral Ucar & Dalbert, 2018). Differences in PBJW between various countries have often been studied but were not significant (Alves, Gangloff, & Umlauft, 2018; Social Justice Research (2020) 33:428-453 Correia & Dalbert, 2007;.…”
Section: Cross-national Differencesmentioning
confidence: 99%
“…In line with this reasoning, individuals who strongly endorsed BJW felt more justly treated by others. For example, students with a strong BJW rated their classmates and teachers as fair (e.g., Correia & Dalbert, 2007;Münscher et al, 2020) and BJW was especially important for disadvantaged students in evaluating their teachers as more just over time (Kiral Ucar & Dalbert, 2020).…”
Section: Belief In a Just Worldmentioning
confidence: 99%
“…It contributes to positive attitudes toward the political and economic system by framing material and legal inequalities as just and fair. Empirical evidence supports the same causal direction, with studies showing that BJW longitudinally forms justice perceptions in more specific areas of life (Dalbert & Stoeber, 2006; Kiral Ucar & Dalbert, 2020). Experimental studies also confirm that people with stronger BJW tend to react to injustices in a different manner than those with lower levels of BJW, which also supports the causal influence of BJW on justice perceptions (Ellard & Bates, 1990; van den Bos & Maas, 2009).…”
Section: Discussionmentioning
confidence: 83%